Aplicación del juego educativo en el proceso de enseñanza aprendizaje para desarrollar destrezas con criterios de desempeño en el área de matemática, módulo 5 mi casa grande: Ecuador, bloques numérico y de medida, con los niños de tercer grado de la escuela de educación básica Lauro Damerval Ayora n° 2, de la ciudad y provincia de Loja, periodo lectivo 2013-2014 - Tamayo Cordero, Millan Rene (2015)
In the research entitled: IMPLEMENTATION OF EDUCATIONAL GAME IN THE TEACHING LEARNING TO DEVELOP SKILLS WITH PERFORMANCE CRITERIA IN THE AREA OF MATHEMATICS, MODULE 5 "MI CASA GRANDE: ECUADOR", NUMBER AND MEASURING BLOCKS WITH CHILDREN THIRD GRADE SCHOOL OF BASIC EDUCATION "LAURO Damerval AYORA No. 2", the city and province of Loja, academic period 2013-2014 general objective: To determine the importance of implementing the educational game in the teaching process learning to develop skills with performance criteria in the area of mathematics, Module 5 "my big house: Ecuador", numerical and measurement blocks, with third graders basic school education "Lauro Damerval Ayora No. 2" , city and province of Loja, academic year 2013-2014, to contribute to the improvement of education in our city, province and country. This research is quasi - experimental development and comprehensive, analytical, deductive, scientific, participatory approach, proactive workshop model and comprehensive evaluation was used; between technique and instrument used it consisted of a survey with its own same questionnaire was applied to a teacher and 12 students of the third grade of General Basic Education, also a diagnostic to third graders evaluation was applied. After the analysis and interpretation of the results, it has been determined that: There is no proper implementation of educational games, so the third graders have failed to develop fully the skills to performance criteria the area of mathematics at the Module 5, numerical and measurement blocks, these results are the result of the implementation of the survey to children and teachers of third grade, so it is concluded that the low level of use of educational games do not allow the development of fully criteria of performance skills of children which evidence could be in the coefficient of correlation between the diagnostic evaluation and the final assessment, resulting in 0.66 equivalent to a high correlation demonstrates that the application of educational games has a great influence in developing skills with performance criteria.